Technology expertise of creating a site of discourse (Eurasian Journal of Philology Science and Education, 2018)
The annotated article, the author examines the technology to create a site examination of discourse. For this purpose demonstrates the system of indicators, consisting of sub-strategies nomination, goal-setting, evaluation. The main instrument of this technology becomes information, born on the basis of explicit and implicit meanings of discourse and explicable KPI system.